1990
DOI: 10.1042/bj2720377
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aluminium on iron uptake and transferrin-receptor expression by human erythroleukaemia K562 cells

Abstract: Incubation of human erythroleukaemia K562 cells with Al-transferrin inhibited iron uptake from 59Fe-transferrin by about 80%. The inhibition was greater than that produced by a similar quantity of Fe-transferrin. Preincubation of cells for 6 h with either Al-transferrin or Fe-transferrin diminished the number of surface transferrin receptors by about 40% compared with cells preincubated with apo-transferrin. Al-transferrin did not compete significantly with Fe-transferrin for transferrin receptors and, when ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…As soluble TfR represents a valuable quantitative assay of marrow erythropoietic activity [27], we concluded that aluminum could inhibit hemopoiesis. Sheila et al [28] reported that Al reduced the number of surface-binding sites for TF, but Yamanaka et al [29] reported that Al induced the Fe response element to bind to the active site of IRP2 by competitively inhibiting the oxidative modification of the protein with Fe, which increases mTfR biosynthesis. The effect of Al on sTfR biosynthesis is controversial and still needs further research.…”
Section: Discussionmentioning
confidence: 98%
“…As soluble TfR represents a valuable quantitative assay of marrow erythropoietic activity [27], we concluded that aluminum could inhibit hemopoiesis. Sheila et al [28] reported that Al reduced the number of surface-binding sites for TF, but Yamanaka et al [29] reported that Al induced the Fe response element to bind to the active site of IRP2 by competitively inhibiting the oxidative modification of the protein with Fe, which increases mTfR biosynthesis. The effect of Al on sTfR biosynthesis is controversial and still needs further research.…”
Section: Discussionmentioning
confidence: 98%
“…(1) In apoTf (open form), the residue Asp229 of the N2-subdomain is in contact with the Lys591 of the C1-subdomain, and thereby Asp229 in the apoTf is buried in the protein, while in Fe 2 Tf (closed form), the residue Asp229 separates from the Lys591 and is exposed by the movement of the N2-subdomain upon iron binding. (2) In apoTf, the residue Glu654 of the C1-subdomain is in contact with the Leu564 of the C2-subdomain by van der Waals force, and in Fe 2 Tf, the Glu654 is exposed by the movement of the C2-subdomain upon Fe 2 Tf forming. (3) In the apoTf open form, the residue Glu318 is located below the ionic bond of Asp240 in the N2-subdomain and Arg678 in the C-terminal, while in the Fe 2 Tf closed form, the residue Glu318 is disclosed because of the disruption of the Asp240-Arg678 bond by the movement of the N2-subdomains, resulting in the formation of a large ΔSASA of approximately 80 Å 2 .…”
Section: Ce Analysis For Tf and Tfrmentioning
confidence: 99%
“…However, aluminum, which is a neurotoxicant, inhibits more than 200 biologically important functions and causes various adverse effects [1]: It is associated with dialysis dementia, and its toxicity may cause nephritic disorders, pulmonary fibrosis, etc. [2][3][4][5][6][7]. In particular, aluminum is suspected to be involved with neurodegenerative diseases such as Alzheimer's disease; however, its role in such diseases is not clear [4,8].…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies [12][13][14][15] on A1 and anemia of dialysis patients suggest that when Al is bound to transferrin [12] it inhibits iron uptake at the cellular level partly by down regulating transferrin receptor expression and partly by interfering with the intracellular release of iron from transferrin [13], By interfering with the bioavailability of iron [13], Al accumulation may cause microcytic anemia and reduce the rate of ervthropoiesis by interfering with some of the key rate-limiting enzymes of heme synthesis [14,15], In dialysis patients, Al accumulation is mostly due to gastrointestinal absorption in Al-containing diets and drugs after water treatment which is often done worldwide. The factors [16.…”
Section: Discussionmentioning
confidence: 99%